The Zionist Entity’s Violations Of The Rules For Protecting Medical Facilities In Gaza - النعيمي ياسمين; مايا شوكت صفطلي (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The Gaza Strip is part of the occupied Palestinian territories that were occupied as a result of the hostilities in the 1967 war, and accordingly the Zionist entity has an obligation to implement the provisions of international humanitarian law based on its being an occupying authority on the one hand, and on the one hand it is an occupying. On the other hand, it is state party to the fourth Geneva convention of 1949. Despite this, it is noted that it always commit many violations of the rules of this law, the most serious of which is the violations that affect medical facilities, given that they are allocated under the rules of international humanitarian law with special protection, in addition to… the general protection provided for all civilian objects during situations of armed conflict. This is due to several considerations, the most important of which is that these facilities fall within the scope of objects that are indispensable for preserving the health and life of civilians. Treatment and health care for sick and wounded civilians cannot be provided except through them, which is imperative. Granting this type of protection to it, not for its own sake, but rather as ancillary to protecting civilians.